ANALISIS STRATEGI NABI YUSUF A.S. DALAM MENGHADAPI ANCAMAN KRISIS PANGAN - BIN BAKAR, YUSRAN; TANJUNG, HENDRI; IBDALSYAH, IBDALSYAH (Kasaba, 2021)
The story of Prophet Yusuf (Joseph) is considered the best story due to the multitude of lessons it offers, applicable at individual, family, community, and state levels. One crucial lesson revolves around Prophet Yusuf's character, demonstrating traits such as integrity, adherence to principles, resilience against temptations, sincerity in serving the nation, competence in treasury management, and knowledge of his responsibilities. Additionally, forgiveness towards those who wronged him exemplifies a pure heart. Another key lesson is the unwavering support extended by the king to Prophet Yusuf, appointing him as a trusted advisor and treasury official with authority over the entire kingdom. Prophet Yusuf's strategic actions during the seven-year famine, serving to save the Egyptians from the crisis, emphasized the importance of assessing threats, raising awareness, planning and executing steps, prudent resource management, fostering community involvement, and maintaining morale over a prolonged period. Ultimately, the success of government initiatives, as seen through Prophet Yusuf's story, hinges on four essential elements working in harmony: a strong and trustworthy leader, robust governmental backing, a well-defined program, and active cooperation and participation from the people. By synergizing these elements, a government can effectively implement and maximize the impact of its programs. The narrative of Prophet Yusuf serves as a valuable guide for individuals and nations alike, showcasing timeless advice on leadership, governance, crisis management, community resilience, and the significance of unity in achieving common goals.